1997
DOI: 10.1099/0022-1317-78-1-163
|View full text |Cite
|
Sign up to set email alerts
|

Activity of JC virus archetype and PML-type regulatory regions in glial cells.

Abstract: Sequence variations are seen in the JC virus promoter/enhancer in virus taken from progressive multifocal leukoencephalopathy (PML) brains and it has been hypothesized that the variations arise in the host at some point in the development of PML. These rearrangements may be adaptations for enhanced growth in glial cells ; if so, transcription or replication levels should differ between archetypal and rearranged PML-type promoters. The archetype and four PML-type promoters were analysed in human glial cells for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
(43 reference statements)
2
31
0
Order By: Relevance
“…DNA sequence analysis showed 100% homology with the Tag region of JCV Mad-1 strain. The high heterogeneity of the JCV regulatory region observed by several groups in human PML cases may account for the negative PCR data obtained with the oligonucleotides employed in this study [38,47].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…DNA sequence analysis showed 100% homology with the Tag region of JCV Mad-1 strain. The high heterogeneity of the JCV regulatory region observed by several groups in human PML cases may account for the negative PCR data obtained with the oligonucleotides employed in this study [38,47].…”
Section: Discussionmentioning
confidence: 85%
“…The JCV regulatory region of sample 50 may have arisen from a crossingover between JCV archetype and Mad-1 strains. Although many JCV variants can be detected in human specimens [38,47], this speci®c alteration of the JCV regulatory sequence has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report demonstrated that the 23-bp insert played a role in the inactivity of the archetype late promoter [91]. The archetype late promoter also appeared to be less responsive to any T protein-induced shift from early to late activity [92]. With no suitable animal models that induce PML-like symptoms from a JCV infection and the inability to show biological activity of archetype virions in vitro, questions remain as to the nucleotide sequence structure of the JCV regulatory region in relation to polyomavirus evolution and PML pathogenesis.…”
Section: Jcv Genomic Variantsmentioning
confidence: 99%
“…Although NCCRs containing repeats (such as Mad-1 or Mad-4) and variants isolated from PML strains have greater transcriptional activity in PDA cells (173), both the archetype and various PML isolates show increased transcriptional activity in glial cells rather than cells of nonglial origin (23,464). Once T antigen is present, the difference in replication fitness between different variants of JCV becomes much less apparent (23). Therefore, the ability of the virus to transcribe the early side of its genome is a major determinant of cell type specificity of the virus and has been the focus of much of the research on viral transcription.…”
Section: Transcription Of Jcv Genesmentioning
confidence: 99%